Molecular and phenotypic characterization of Escherichia coli from calves in an important meat-producing region in Brazil - Juliane F Tutija; Carlos AN Ramos; Ricardo AA Lemos; Amanda AL Santos; Guilherme H Reckziegel; Mariana G Freitas; Cassia RB Leal (Journal of Infection in Developing Countries)
Introduction: Escherichia coli strains that lead to enteritis are considered an important cause of diarrhea in calves. For correct identification, these microorganisms must be differentiated from non-pathogenic members of the intestinal microbiota. The aim of the present work was to characterize E. coli isolates in calves regarding the presence of virulence genes that cause enteritis and evaluate the sensitivity of the isolates to different antimicrobials.